2021
DOI: 10.1371/journal.pone.0246295
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and biochemical abnormalities associated with severe forms of COVID-19: A retrospective single-center study from Morocco

Abstract: Since December 2019, the coronavirus disease (COVID-19) pandemic has catapulted the world into a marked health crisis, with over 29 million cases and >930,000 deaths. To better detect affected individuals at an early stage and stop disease progression to an advanced stage, several studies have been conducted to identify the clinical, biological, and radiological characteristics of COVID-19. This study aimed to enrich the literature by critically analyzing the clinical and biological characteristics of 134 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 30 publications
5
27
0
1
Order By: Relevance
“…To see the association between chronic illness and biochemical abnormalities, we conducted chi-square test which revealed that all the biochemical abnormalities were significantly associated with cardiac and endocrine diseases (p<0.05). Several studies and review conducted at China, Italy, Iran, Morocco, India, Iraq, UAE, USA revealed that various biochemical abnormalities are more prevalent among the COVID-19 patients with pre-existing comorbidities like hypertension, ischemic heart disease, diabetes which is similar to our study as well 23,[25][26][27][28][29][30][31] .…”
Section: Resultssupporting
confidence: 88%
“…To see the association between chronic illness and biochemical abnormalities, we conducted chi-square test which revealed that all the biochemical abnormalities were significantly associated with cardiac and endocrine diseases (p<0.05). Several studies and review conducted at China, Italy, Iran, Morocco, India, Iraq, UAE, USA revealed that various biochemical abnormalities are more prevalent among the COVID-19 patients with pre-existing comorbidities like hypertension, ischemic heart disease, diabetes which is similar to our study as well 23,[25][26][27][28][29][30][31] .…”
Section: Resultssupporting
confidence: 88%
“…Studies of CRP levels in association with COVID-19 in Africa appear to be rare, but the metabolic marker may not be rare. Some reports indicated that CRP levels were associated with adverse outcomes in patients [89][90][91]. In general, CRP levels are high in many African countries or in African Americans, especially in association with diabetes, hypertension, or infectious diseases [92].…”
Section: C-reactive Protein (Crp)mentioning
confidence: 99%
“…These results are in concordance with the findings of other researchers. [ 13 14 15 16 17 18 19 20 21 22 23 24 25 ] Waris et al . [ 26 ] also demonstrated similar results except that they did not find a significant association between disease severity and lymphocytopenia ( P value = 0.28).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, serum CRP, ferritin and LDH were significantly high in patients with severe disease. Our findings were in concordance with the results of Shang et al .,[ 13 ] Ding et al .,[ 14 ] Keski et al .,[ 15 ] Kantri et al .,[ 17 ] Bhandari et al .,[ 19 ] Asan et al .,[ 20 ] Nizami et al .,[ 22 ] Asghar et al . [ 23 ] and Rahman et al .…”
Section: Discussionmentioning
confidence: 99%